2014
DOI: 10.1002/ajim.22330
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression of pleural disease due to exposure to Libby amphibole: “Not your grandfather's asbestos related disease”

Abstract: LA exposure can cause a non-malignant pleural disease that is more rapidly progressive and more severe than the usual asbestos-related disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…We recently demonstrated that the LA-induced autoantibodies alone, in the absence of asbestos, could contribute to the fibrotic process in mice (Gilmer et al 2016). The public health significance of this result is further highlighted by evidence that the LA non-malignant pleural disease is more severe and progressive than what is classically described for general occupational (chrysotile) asbestos exposures, and that the radiographic lesions were clearly associated with pulmonary function decline (Black et al 2014, Larson et al 2012, Whitehouse 2004). …”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…We recently demonstrated that the LA-induced autoantibodies alone, in the absence of asbestos, could contribute to the fibrotic process in mice (Gilmer et al 2016). The public health significance of this result is further highlighted by evidence that the LA non-malignant pleural disease is more severe and progressive than what is classically described for general occupational (chrysotile) asbestos exposures, and that the radiographic lesions were clearly associated with pulmonary function decline (Black et al 2014, Larson et al 2012, Whitehouse 2004). …”
Section: Introductionmentioning
confidence: 77%
“…Vermiculite is a mineral well known for its ability to resist changes in temperature and degradation, making this silicate mineral desirable for use in many products. Unfortunately, the vermiculite ore bed was contaminated with a unique type of amphibole asbestos now referred to as Libby Amphibole (LA) (Black et al 2014). Many public structures in Libby were conditioned with this mineral, including homes, playgrounds, and the track and baseball field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings have included the associations between X-ray and spirometry [Larson et al, 2012], low-level exposure and PT [Rohs et al, 2008;Christensen et al, 2013], exposure severity and PT [Rohs et al, 2008] and exposure and asbestos-related mortality, including mesothelioma [Sullivan, 2007;Whitehouse et al, 2008]. Informative as these reports are, they reflect our grandparental knowledge of ARD and not the unique features described by Black et al [2014] in this issue of the AJIM. Among 353 patients with X-rays indeterminate for PT, 98 (28%) were noted to have PT on HRCT [Muravov et al, 2005].…”
mentioning
confidence: 99%